Digital Art History. (3rd April 2019) - Baca, Murtha; Helmreich, Anne; Gill, Melissa
Abstract : This introduction frames and situates this special issue of Visual Resources on the topic of digital art history, intentionally assembled five years after the journal's previous digital art history issue with the goal of assessing the progress made in the field and encouraging more widespread adoption of digital methodologies. It sets forth the key themes of this issue: "thought pieces" on the state of digital art history and its value for scholarship and pedagogy; the significance of databases for art history and the intellectual complexities they entail; innovative computational analysis applied to material and social-historical questions in art history; and the possibilities engendered by online publishing. These foci are developed through and grounded in critically informed scholarly projects in digital art history. These projects also bring to light professional, cultural, social, linguistic, and even political issues encountered in practicing digital art history.